RESEARCH ON DYNAMIC CHARACTERISTICS OF WIND TURBINE MAIN SHAFT BEARING UNDER DIFFERENT WORKING CONDITIONS - ZHANG Juan; ZHAO RongZhen; YU RongPeng; LIU Hong; ZHANG YaLong (Jixie qiangdu, 2017)
In order to get the dynamic characteristics of wind turbinemain shaft bearing under different working conditions,tooka 1. 5 MW wind turbine manufactured by one turbine factoryas an example,the main shaftwassimplifiedabstractly and the axial and radial loadon main shaft bearingwere given by blade element theory. The 3 D model of main shaft bearingwasdrawn in UG and imported into ADAMS toestablish the multi rigid kinetic model of main shaft bearing,the interactionsbetween the balls of main shaft bearing and inner ring,outer ring and separator wereanalyzed under threedifferent working conditions. The analysis resultsindicate that the interaction forces between the balls of main shaft bearing and inner ring,outer ring and separator aremaximal during theemergency brake period of wind turbine,it is second during thesuddenvariation periodof the wind turbine revolving speedand it is minimalfrom starting until running steadily.